1997
DOI: 10.1038/bjc.1997.482
|View full text |Cite
|
Sign up to set email alerts
|

Tumour cells of extramammary Paget's disease do not show either p53 mutation or allelic loss at several selected loci implicated in other cancers

Abstract: Summary Extramammary Paget's disease is a particular form of skin cancer of unknown histogenesis. To look for the genetic defects underlying the pathogenesis of this tumour, we have examined loss of heterozygosity (LOH), p53 and human papillomavirus (HPV) status, and the expression of c-erbB-2 and bcl-2 proteins in 14 cases. Unexpectedly, no LOH was detected at several loci commonly lost in other human cancers (namely 3p, 9p, 9q, 13q, 16q, 17p, and 17q) in 12 tumours examined. Altered p53 protein expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…8,9,[12][13][14] PCR studies for HPV have also been reported as negative in all mammary and extramammary Paget's disease (20/20 and 14/14 cases, respectively). 15,16 Although most of our cases of anal Paget's disease were positive for ProExtC, HPV type 16 was detected by PCR in one case where 75% of Paget cells stained positive. This case did not show histologic changes diagnostic of HPV nor was HPV DNA detected by in situ hybridization.…”
Section: Discussionmentioning
confidence: 72%
“…8,9,[12][13][14] PCR studies for HPV have also been reported as negative in all mammary and extramammary Paget's disease (20/20 and 14/14 cases, respectively). 15,16 Although most of our cases of anal Paget's disease were positive for ProExtC, HPV type 16 was detected by PCR in one case where 75% of Paget cells stained positive. This case did not show histologic changes diagnostic of HPV nor was HPV DNA detected by in situ hybridization.…”
Section: Discussionmentioning
confidence: 72%
“…No study has evidenced human papillomavirus (HPV) antigen or HPV DNA in the cells of vulvar Paget disease specimens [42,[86][87][88][89], so that the participation of HPV infection in the pathogenesis of the disease is unlikely. On the other hand neither p53 gene mutations nor loss of heterozygosity at selected loci were detected in Paget cells [89]. Immunohistochemical analyses for c-erb-B2 antigen [22,30,90], bcl2, and p53 protein expression [59,84,91,92] have revealed conflicting and inconclusive results.…”
Section: Viruses Oncogenes and Tumor Markersmentioning
confidence: 99%
“…Tumor tissue was isolated from 5 to 10 consecutive 6 m frozen tissue sections by microdissection, and genomic DNA was isolated according to standard methods by proteinase K digestion and phenol-chloroform extraction (Takata et al, 1997). Exons 2 to 8 of the androgen receptor gene were amplified using primers and PCR conditions as described previously (Tilley et al, 1996).…”
Section: Dna Sequencingmentioning
confidence: 99%
“…We previously showed that erbB-2 overexpression by either gene amplification or transcriptional activation may play a part in the progression of EMPD (Takata et al, 1999). However, other molecular genetic defects, including p53 mutations, allelic loss of several selected chromosome arms as well as abnormal activation of the ␤-catenin gene, which are commonly seen in other epithelial malignancies, were not detected in EMPD (Takata et al, 1999;Takata et al, 1997). To explore further the molecular pathogenesis of EMPD, we aimed at examining androgen receptor expression in Paget's cells of EMPD for several reasons.…”
mentioning
confidence: 99%